GENE-57. COMPARATIVE MOLECULAR LIFE HISTORY OF SPONTANEOUS CANINE AND HUMAN GLIOMA. (11th November 2019) - Amin, Samirkumar; Anderson, Kevin; Bourdreau, Beth; Martínez, Emmanuel; Kocakavuk, Emre; Johnson, Kevin C; Barthel, Floris; Varn, Frederick; Kassab, Cynthia; Ling, Xiaoyang; Kim, Hoon; Barther, Mary; et al.
Abstract: Diffuse gliomas are the commonest of malignant brain tumors with high-grade tumors carrying dismal prognosis. Preclinical models have proven themselves as poor predictors of clinical efficacy, attributed to the lack of a comparable tumor microenvironment. Comparative genomics of canine and human gliomas provide an attractive alternative modality to identify conserved drivers and underlying mutational processes of glioma as well as evaluate life history tradeoffs related to tissue context and aging that can shape type and relative timing of drivers in gliomagenesis. We performed a comparative genomics analysis between whole genome-, exome-, transcriptome- and methylation-sequencing of 77 canine gliomas, and human pediatric (n=217) and adult gliomas (n=822). We found alterations in common with those in human pediatric and adult gliomas in the Tp53 and cell cycle pathways, receptor tyrosine kinase and Idh1 R132 mutations. Canine gliomas showed similarity to human pediatric gliomas in terms of lower mutational rates (0.2–0.29 per megabase), hotspot mutations and amplifications of Pdgfr α, and robust aneuploidy constrained within the syntenic regions of Pdgfr α and Myc, but also in the known pediatric drivers, Hist1 and Acvr1 genes. A mutational signature reflecting homologous repair defect was detected in canine and pediatric but not adult gliomas, potentially resulting in the observed higher rates of genomic instability. Canine gliomas in majority classified as pediatric tumors using a commonly used human brain methylation classifier (Capper et al. 2018) and cell-of-origin analysis by deconvoluting canine transcriptome using lineage-specific gene signatures. By providing a large canine glioma genomic-sequencing dataset and comparing it with human glioma, our study provides unique insights into glioma etiology and the chronology of glioma-causing somatic alterations. Further, our results effectively position preclinical models of spontaneous canine glioma for use in understanding glioma drivers, and evaluate novel therapies targeting aneuploidy, especially for pediatric brain tumors.